A internacionalização da pós-graduação: um estudo de caso da Universidade Federal de Santa Maria - Della Méa, Liliane Gontan Timm (2013)
This study is based in the origins of Higher Education in Brazil, highlighting its expansion and regulation in order to situate the rise of the Post Graduation and its evaluation made by the agency CAPES. In the context of pursuing qualification, it s addressed the National Evaluation System of Higher Education (SINAES) and the Evaluation System of Brazilian Post Graduation, developed by CAPES, in which the internationalization is mentioned as a qualification benchmark. Based in these elements, the demand for internationalization can be considered as one of the most meaningful impact in the evaluation of Post Graduation Program. This study aims to identify the demand for internationalization in the Post Graduation Programs of UFSM, graded 5 or above by CAPES. The focus of the study was the Doctoral Courses. The qualitative method of case study was used and the documents of the area, the evaluation form, the self-evaluation and the interviews conducted with the Coordinators/Managers regarding internationalization were analyzed. The results identified that there is a great concern in the Programs in becoming internationalized, through the development of its excellence in the strengthening of international partnerships, exchange programs, qualification for its faculty with post doctoral courses and short term internships abroad and especially in the increasing of its international publications. It is intended to provide subsidies to the decision making for maintenance, perfecting and strengthening of the institution and its Post Graduation Courses.